Environmental Information System for Disaster Risk Management at Kota Surakarta - Sunarhadi, R. Muhammad Amin; Setyono, Prabang; Kusumaningrum, Lia; Kurniaaji, Bayu; Ally, Haydar; Ahsani Taqwim, Muhammad Hanif; Ulhaq Fil'ardiani, Nida; Achmad Zaky, Fadhil; Abdul Jabbar, Sa'ad (Universitas Veteran Bangun Nusantara, 2023)
Through this activity, disaster volunteers in Surakarta City can conduct disaster risk reduction (DRR) efforts based on ecosystem data and information management. Climate change has an increasing impact on ecosystems, resulting in environmental damage, thereby increasing the intensity of disaster events that need to be studied and monitored. Managing this disaster risk data and information requires using an environmental information system for ecosystem-based disaster risk reduction (ECO-DRR). The capacity of volunteers is vital in dealing with the risks of natural disasters and the impact of climate change by using SIL. Currently, volunteers manage using a form that has yet to accompany the presentation of information for decision-making and management of disaster risk knowledge. Requires remedial action by increasing the ability of volunteers to manage disaster risk data and information, report disaster events, and present them in dashboards. The method used is the parameters for development of SIL as a solution for ecosystem-based disaster risk reduction (ECO-PRB). The parameters were conducted on the topics of disaster risk, disaster incident reporting, and dashboard information management. The development of ECO-DRR SIL uses Quality Function Deployment (QFD) to obtain information on improvements in developing a user-based digital platform.